Resilience to depression: Implication for psychological vaccination - Dai, Qin; Smith, Graeme D. (Frontiers in Psychiatry, 2023)
From the vulnerability perspective, we often ask the question “why someone suffers from depression?” Despite outstanding achievements along this line, we still face high occurrence or recurrence and unsatisfied therapeutic efficacy of depression, suggesting that solely focusing on vulnerability perspective is insufficient to prevent and cure depression. Importantly, although experiencing same adversity, most people do not suffer from depression but manifest certain resilience, which could be used to prevent and cure depression, however, the systematic review is still lack. Here, we propose the concept “resilience to depression” to emphasize resilient diathesis against depression, by asking the question “why someone is exempted from depression?” Research evidence of resilience to depression has been reviewed systematically: positive cognitive style (clear purpose in life, hopefulness, et al.), positive emotion (emotional stability, et al.), adaptive behavior (extraversion, internal self-control, et al.), strong social interaction (gratitude and love, et al.), and neural foundation (dopamine circuit, et al.). Inspired by these evidence, “psychological vaccination” could be achieved by well-known real-world natural-stress vaccination (mild, controllable, and adaptive of stress, with help from parents or leaders) or newly developed “clinical vaccination” (positive activity intervention for current depression, preventive cognitive therapy for remitted depression, et al.), both of which aim to enhance the resilient psychological diathesis against depression, through events or training. Potential neural circuit vaccination was further discussed. This review calls for directing attention to resilient diathesis against depression, which offers a new thinking “psychological vaccination” in both prevention and therapy of depression.